HUBUNGAN KEBIASAAN KONSUMSI NATRIUM DAN PERSEN LEMAK TUBUH DENGAN TEKANAN DARAH: THE RELATIONSHIP OF SODIUM CONSUMPTION HABITS AND BODYFAT PERCENT WITH BLOOD PRESSURE - Alfiani Husna Agira; Taufiq Firdaus Al Ghifari Atmadja; Luh Desi Puspareni (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Introduction: Hypertension is a silent killer disease that triggers cardiovascular disease. Risk factors of hypertension that can be modified are sodium intake and body fat percent. Objective: This research aims to analyze the relationship between sodium consumption habits and body fat percent with blood pressure on hypertensive patients at Kahuripan Health Center in 2024. Materials and Methods: This research desain is an analytical observational with cross sectional approach that carried out at the Integrated Development Post (Posbindu) in Kahuripan Health Center. The sampling technique in thisresearch used is Purposive Random Sampling. The research respondents are 91 hypertensive patients aged >18 years and <60 years. The instruments of this research are the respondent characteristics questionnaire, Semi Quantitative Food Frequency (SQ-FFQ), Bioelectrical Impedance Analysis (BIA), and sphygmomanometer. Data were analyzed by Chi-Square statistical test. Results: The results of this study showed that the majority of respondents had hypertension, namely 64 people (70,3%). Respondents have an excessive sodium consumption habits (56%) and excessive body fat percent (88%). There is a relationship between sodium consumption habits and blood pressure in hypertensive patients (p=0,001) and there is no relationship between body fat percent and blood pressure in hypertensive patients (p=0,209). Conclusions: There is a relationship between sodium consumption habits and blood pressure in hypertensive patients. Hypertension patients are suggested to always maintain their diet, regularly take hypertension medication, and check their blood pressure at the nearest Integrated Development Post (Posbindu) even if there are no symptoms of hypertension. Keywords : Hypertension, Sodium, Body Fat Percent